Standard operating procedures on trafficking in persons for commercial sexual exploitation (New Delhi, 2016)
Arz (anyay rahit zindagi) is an organization working to combat human trafficking for commercial sexual exploitation. Over the years of working on the issue, we have found that the law enforcement agencies and service providers, especially the front-line workers, are not well versed with the standard procedures to be followed. Furthermore, the law enforcement agencies have neither the resources nor the time to refer to the numerous legislations, rules, advisories and judgments dealing with the issue. This lack of knowledge results in them not following mandatory provisions, as a result of which they on one hand violate the rights of the victim and on the other make it more difficult for the victim to get justice. The front-line workers need to have this information readily accessible if they are to work more effectively with the victims.
Keywords: Sexual Exploitation